Sociological Understanding of Muslim Education in Multicultural Philippines - Abdul Haiy Abdul Sali (Dinamika Ilmu, 2023)
The DepEd Order No. 41, s. 2017 catapulted the implementation of the Arabic Language and Islamic Values Education (ALIVE) Program. However, since its inception, there is a dearth of professional literature on a coherent sociological understanding of Muslim education in the Philippines. This paper aims to provide an understanding of the implementation challenges of the ALIVE program employing sociological perspectives. The study utilized a qualitative research method anchored on Case Study Research Model. Five ALIVE implementers in Metro Manila were part of the research participants. A thematic analysis was initiated and triangulation of data was employed from relevant data sources. The analysis results showed several challenges faced by the select ALIVE schools: The intended curriculum lacks appreciation of the approaches and evaluation of student learning. The scarcity of learning spaces was evident. In teaching, most of the Asatidz or Madrasah teachers require enhancement of their pedagogical competence. The cultural variance among Muslims is still evident, especially in non-Muslim communities. The findings indicate that there is a need to create deliberate plans to achieve the intended learning outcomes of the ALIVE Program. Given the various gaps and challenges identified in this study, there is a necessity to evaluate the program at the grassroots. In conclusion, maximizing and strengthening the participation of the various stakeholders and different sectors in society is imperative in the development and sustainability of Muslim education programs in the Philippines.